Utilization of Web Based Research Management Applications for Research by Postgraduate Students of Business Education in South East, Nigeria - Ngozi; Stella (Journal of Research in Industrial Technology and Educational Studies, 2026)
This study investigated the utilization of web-based research management applications by postgraduate students of Business Education in South-East Nigeria. One research question guided the study and one hypothesis was tested. A descriptive survey design was employed, covering the entire population of 141 postgraduate students from six public universities. Data were collected using a structured questionnaire and analyzed with mean, standard deviation, and t-test statistics at a 0.05 significance level. The results showed that students use web-based research management applications to a moderate extent. Further findings revealed that gender significantly affected usage, with male students using the tools more than female students, while age had no significant effect. The study concluded that postgraduate students of Business Education in South-East Nigeria utilize web-based research management applications to a moderate extent. Based on these findings, the study recommended among others that administrators of universities and departments of Business Education should organize regular workshops and training sessions to improve postgraduate students’ awareness and competence in the use of web-based research management applications such as Mendeley, Zotero, and EndNote.
Keywords: Application; web-based Research amanagement; Postgraduate students; business education; research